Vous êtes sur la page 1sur 1

TRABAJO PRÁCTICO LÍMITES

3x 2 - 4 x + 1 3x 4 - 2 x x -1 x3 + 6 x 2 + 12 x + 8
1) lim = 2) lim = 3) lim = 4) lim =
x �2 2x - 2 x �0 2 x - 1 x �1 2x - 2 x �2 x 2 + 3x + 2

x2 - x - 6 2x2 - x - 3 x-4 x-4


5) lim 2 = 6) lim 2 = 7) lim = 8) lim =
x �3 x + x - 12 x � -1 x - x - 2 x �4 x 2 - 16 x �4 x -2

x 3 + x 2 - 16 x + 20 y5 + 1 x 5 + 32 x3 - 64
9) lim = 10) lim = 11) lim = 12) lim 2 =
y � -1 y 2 - 1
x �2 x 2 - 3x + 2 x � -2 x 2 - 4 x �4 x - 8 x + 16

sin 4 x sin 7 x x-2 x 4 - 81


13) lim = 14) lim = 15) lim = 16) lim =
x �0 8x x �0 tg 5 x x �2 2- x - x-2 x �3 x 3 - 27

17) lim
x3 - 1
x �1 2 x - 2
a 2 - 2a
= 18) lim 2
a �2 a - 4
= 19) lim
x �3
(
x 2 + 5 10 x + 2 = ) 20) lim
x �0
x
1 + x2 - 1
=

sen3 x 7 x 2 - 3x 7 -3 x 2 + 2 x 3 7
21) lim = 22) lim 3 = 23) lim = 24) lim =
x �� 5 x - 2 x x �� 7 x 3 - 4 x x �� x + 1
x �0 x

-3 x 2 + 8 x + 1 2x - 3 3x
25) lim = 26) lim = 27) lim =
x �� 9 x 2 - 2 x + 4 x �� 3 x + 2 x 2 - 1
4 x ��
x +4+4
2

x
2x -1 3�
2x
x.tgx
28) lim = 29) lim �1 + � = 30) lim � +
1 �
2
31) lim =
x ��
4x + x - x
2 x ��

� x� �1 �= x �0 senx
x ��
� 3x �

2x
x 2 + 7 x + 10 x 2x - 5 � 4 �
32) lim = 33) lim = 34) lim = 35) lim �1+ � =
x �� 2 x + 3
x � -2 x+2 x �0 sen 2 x x ��
� 3x �

x3 + x 2 - x - 1 x+3 - 3 x2 - 4x +1
36) lim = 37) lim = 38) lim =
x � -1 x2 - x - 2 x �0 x x �5 x -5

39) lim
x �3
x2 - 2 x + 3
x2 - 9
= 40) lim 2
x3 - 1
x �1 x - 1
= 41) lim
x �3
(
x2 + x + 1 = )
5x2
=
5x - 3
=
( y - 1) ( y 2 + 2 y - 3)
42) lim 43) lim 2 44) lim =
x �� 7 x - 3 x
x ��
2x2 - 3 + x y �1 y2 - 2 y +1

45) lim
( w + 2 ) ( w2 - w - 6 )
=
w � -2 w2 + 4 w + 4